A follow‐up study to a randomised control trial to investigate the perceived impact of mindfulness on academic performance in university students. - Bóo, Sebastian J. M.; Childs‐Fegredo, Jasmine; Cooney, Steven; Datta, Bella; Dufour, Géraldine; Jones, Peter B.; Galante, Julieta (Counselling & Psychotherapy Research, 2020)
Objectives: Mindfulness research in education has focused on its potential to support student well‐being. There is a paucity of research on the interaction between mindfulness and academic performance (AP). This qualitative study builds on results of the largest randomised control trial of mindfulness in education to date which suggested mindfulness can have mixed effects on academic performance. A more in‐depth understanding of the relationship between mindfulness and academic performance is therefore needed to ascertain if, how and for which students mindfulness facilitates academic performance. The objective of the study was to capture students' perceptions of the impact of mindfulness on their academic performance. Methods: Thematic analysis was applied to data obtained by six in‐depth interviews from three higher and three lower performing undergraduate participants in the mindfulness intervention arm of the Mindful Student Study randomised control trial. Results: Three themes emerged, whereby five students described mindfulness having a positive impact on their academic performance. One student felt mindfulness had an initial negative impact on academic performance. All students felt mindfulness enhanced self‐awareness and self‐regulation of their thinking, feelings and behaviours, and our analysis suggests students perceived these processes underpinned the effect of mindfulness on academic performance. Conclusion: Differences in students' psychological distress and study habits may determine the differing initial impact of mindfulness on academic performance.